Analisis Cerita Pendek Cinta dan Kebohongan Karya Husnul Khotimah ditinjau dari Teori Psikologi Abraham Maslow - Sahrunneza, Nasywa Ahmad Rizal; Kurniawan, Eva Dwi (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2024)
Short stories are literary essays embodying intrinsic and extrinsic elements. The short story "Love and Lies" delves into psychological manifestations indicative of mental illness or disorders in female characters. This research employs Abraham Maslow's hierarchy of human needs theory, as it stratifies the psychological life of human beings into hierarchical needs. Utilizing quantitative descriptive methods, researchers examine the short stories of "Love and Lies" by Husnul Khotimah as the primary data source. Analysis involves an intensive exploration of literary works, identifying and correlating data with Maslow's theory. The novel is scrutinized through the lens of Maslow's hierarchy, encompassing physiological, safety, belongingness and love, esteem, and self-actualization needs. The findings affirm that all five levels are met, concluding that characters in "Love and Lies" fulfill the psychological hierarchy proposed by Maslow.